2022
DOI: 10.21273/horttech04997-21
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Mulch as an Alternative to Polyethylene for Watermelon Production

Abstract: Polyethylene mulch is widely used for vegetable production in the United States as a tool to conserve water, control weeds, and produce earlier and cleaner products (i.e., less attached soil). However, the increasing labor costs for mulch removal and disposal after harvest and soil environmental pollution are major concerns. The objective of this study was to assess fruit yield and quality, mulch deterioration, soil microbial activity, and nutrient changes in ‘Stargazer’ watermelon (Citrullus lanatus) grown wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Furthermore, BDM can improve soil quality by enhancing nutrient content, preserving soil moisture, and increasing the efficiency of nitrogen utilization [21,19]. In studies have shown that nitrate content, as well as the total and active fungal populations in the soil, increased quantitatively in soils with biodegradable mulch compared to polyethylene mulch one year after mulch application [11].…”
Section: Biodegradable Mulch Materials' Impact On Plant Production Fo...mentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, BDM can improve soil quality by enhancing nutrient content, preserving soil moisture, and increasing the efficiency of nitrogen utilization [21,19]. In studies have shown that nitrate content, as well as the total and active fungal populations in the soil, increased quantitatively in soils with biodegradable mulch compared to polyethylene mulch one year after mulch application [11].…”
Section: Biodegradable Mulch Materials' Impact On Plant Production Fo...mentioning
confidence: 99%
“…Due to their potential cost-effectiveness, biodegradable mulch products are becoming more and more valuable. The major conditions for mulch to be deemed biodegradable in the case of organic agriculture are that it is entirely made of bio-based materials and that it is at least 90% biodegradable by soil microorganisms in the field during a 2-year period [11,32]. Biodegradable mulch is typically turned to carbon dioxide, water, and natural compounds by microbial activity in the soil.…”
Section: Evaluating the Cost-effectiveness Of Biodegradable Mulch Mat...mentioning
confidence: 99%
See 3 more Smart Citations